Gillick and the Consent of Minors: Contraceptive Advice and Treatment in New Zealand - Grimwood, Tim (Victoria University of Wellington Law Review, 2009)
The English House of Lords decision in Gillick has dominated the issue of minor capacity to consent for the last 25 years, but the decision has raised more issues and ambiguities than it hoped to solve. The speeches in Gillick, although extrapolated to general issues of minor consent, were made in the context of contraception advice and treatment. In New Zealand there is no legislation or case law determining if and when minors can obtain contraception advice and treatment without parental consent or knowledge. This raises concerns for health professionals' practice and minors' status as patients. This article discusses whether the rulings in Gillick are applicable or even should be applicable to New Zealand with regards to contraception. The article suggests a scheme for giving contraceptive advice and treatment to minors through a modification of Lord Fraser’s guidelines. These modifications have been incorporated into a suggested legislative framework and professional guidelines.